Digital Consumer Behavior and Purchase Decisions on TikTok: Construction of Meaning, Social Validation, and Strategic Implications - Fitri Dewi Afiany (SAINTEKS : Jurnal Sain dan Teknik, 2026)
This study aims to explore in depth the construction of digital consumer behavior meaning in the purchase decision process on the TikTok platform following its strategic integration with Tokopedia. Using a descriptive qualitative approach with phenomenological studies, this research involved 25 informants consisting of active TikTok users from various demographic backgrounds in Indonesia. Data were collected through in-depth interviews and open-ended questionnaires which were then analyzed using data reduction, categorization, and meaning interpretation techniques based on Peter L. Berger's Social Construction of Reality theory. The research findings show that purchasing decisions on TikTok are the result of a dialectic between the externalization of trends, the objectification of digital metrics (likes, reviews, number sold), and the internalization of consumption identity. The Fear of Missing Out (FOMO) phenomenon and social validation (social proof) are proven to be the main drivers that compress traditional purchasing decision stages into an instant and emotional process. The results of this research provide strategic implications for MSME players to adopt authentic storytelling narratives to build trust in a dynamic social commerce ecosystem.